2002
DOI: 10.1016/s0014-2999(02)02421-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of K+ currents of outer hair cells in guinea pig cochlea by fluoxetine

Abstract: The effects of fluoxetine (ProzacR), a widely used antidepressant drug, on K + channel in outer hair cells isolated from guinea pig cochlea were studied using the whole-cell patch clamp technique. Fluoxetine potently inhibited leak K + currents with an IC 50 of 0.78 AM. The inhibition was reversible and voltage-independent. At 45-to 103-fold higher concentrations than the plasma levels, fluoxetine reversibly blocked voltage-activated K + currents. Kinetics of the current in the presence of fluoxetine resembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Airhart et al (2007) showed that zebrafish exposed to fluoxetine exhibit movement disorders, but whether this effect is related to hair cell function in lateral line, vestibular or hearing organs or to other systemic effects is unknown. Fluoxetine can inhibit potassium currents in guinea pig hair cells, an effect not mediated by the serotonin reuptake channel, but rather by blocking the SK-type potassium channel (Bian, et al, 2002; Terstappen, et al, 2003). This suggests that an off-target effect, blockage of potassium channels, may afford hair cells protection from toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Airhart et al (2007) showed that zebrafish exposed to fluoxetine exhibit movement disorders, but whether this effect is related to hair cell function in lateral line, vestibular or hearing organs or to other systemic effects is unknown. Fluoxetine can inhibit potassium currents in guinea pig hair cells, an effect not mediated by the serotonin reuptake channel, but rather by blocking the SK-type potassium channel (Bian, et al, 2002; Terstappen, et al, 2003). This suggests that an off-target effect, blockage of potassium channels, may afford hair cells protection from toxins.…”
Section: Discussionmentioning
confidence: 99%
“…A corollary to this concept is that elevated prestin levels in a mutant OHC would increase this risk. This process could potentiate the large leak currents that are already present in OHCs (Beurg et al 2009;Bian et al 2002;Fuchs 1992;Housley and Ashmore 1992;O'Beirne and Patuzzi 2007), overwhelm a cell's ability to regulate its intracellular ion concentrations, and drive it towards necrosis or apoptosis. As well, there may be other underlying differences in the OHC membrane between Tecta genotypes that affect their susceptibility to electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown to block the effects of intense stress on behaviour and the cardiovascular system in an animal model of post‐traumatic stress disorder . Recent studies have shown that other antidepressant agents, such as fluoxetine, also affect hair follicles in animals . Hence, we decided to investigate the effects of tianeptine on UWS‐induced AA‐like lesions in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Tianeptine is an antidepressant with memory‐protective properties that increases serotonin uptake in the brain. Recent studies have shown that other antidepressant agents, such as fluoxetine, affect the hair follicles in animals . In this study, we investigated whether tianeptine could inhibit the effects of catagen induction in AA‐like lesions induced by ultrasonic wave stress (UWS) in mice.…”
Section: Introductionmentioning
confidence: 99%